2023
DOI: 10.1111/jsr.13890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of homeostatic pressure on daytime vigilance performance: Evidence from behaviour and resting‐state EEG

Abstract: SummaryVigilance is highly sensitive to the time‐of‐day effect and goes through the daytime trough during the period of the post‐noon dip. A midday nap could maintain individuals’ vigilance at an optimal level. Thus, homeostatic sleep pressure is one of the main reasons for the post‐noon dip in daytime vigilance. The current study focussed on the role of homeostatic sleep pressure in the diurnal variation of vigilance performance with normal circadian rhythms and the corresponding neural basis. With 34 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Taken together with the fact that participants experienced only a mild degree of fatigue, this may have contributed to the observed outcomes. Furthermore, other studies have also reported a lack of significant correlation between alpha power and sustained attention following only mild or no sleep loss [ 73 , 77 ]. These findings suggest that induction of severe sleep restriction may be necessary to observe correlations between vigilance and alpha power, which was not the case in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with the fact that participants experienced only a mild degree of fatigue, this may have contributed to the observed outcomes. Furthermore, other studies have also reported a lack of significant correlation between alpha power and sustained attention following only mild or no sleep loss [ 73 , 77 ]. These findings suggest that induction of severe sleep restriction may be necessary to observe correlations between vigilance and alpha power, which was not the case in the current study.…”
Section: Discussionmentioning
confidence: 99%